The Legal Protection for Instrumental Witnesses in Notarial Deeds - Saputra, Azrul (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
Protection of Instrumental Witnesses in Notarial deeds has not been specifically regulated in Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notaries. If it is related to the investigation process regarding a Notarial deed related to a legal case, the Instrumental Witness or witness in the notarial deed will be involved in the investigation process and will be summoned as a witness for questioning. The aim of this research is to find out and analyze the legal protection of witnesses in notarial deeds and also to find out and analyze the role of witnesses in notarial deeds. The method that will be used in this research is a normative juridical research method, which is a way to obtain data from library materials, especially those related to legal issues. This means that the research will discuss normative provisions relating to the protection of witnesses and the notarial sector using the legal and regulatory approach that applies in Indonesia. Protection of Instrumental Witnesses in Notarial deeds has not been specifically regulated in Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notaries. However, in general, Law Number 13 of 2006 concerning Protection of Witnesses and Victims provides legal protection for witnesses, including instrumental witnesses. Especially protection in providing testimony at trials related to criminal cases, such as protection for providing information without pressure, the right to receive legal advice, and other general matters. Keywords: Legal; Instrumental; Protection; Witness.